Peran Academic, Social dan Environment Support pada Intensi Berwirausaha Mahasiswa - Fauzani Fauzani; Suryani Suryani; Rahmawati Rahmawati (LPMP Imperium, 2019)
Purpose- This study aims to analyze the factors that influence the level of student interest in entrepreneurship in terms of contextual namely academic, social and environmental support. Methods- Data was collected through the distribution of questionnaires to 100 students consisting of Islamic Economics and Business Faculty students, and the hypothesis was tested by multiple linear regression. Findings- The students' entrepreneurial intentions to create a business are largely determined primarily from the environment, social and academic support. Implications- This study offers alternative recommendations to universities and policymakers about the entrepreneurial intentions of business students.